Inhalation of marijuana affects drosophila heart function - Gómez, Ivana María (2019)
We investigated the effect of inhalation of vaporized marijuana on cardiac function in Drosophila melanogaster, a suitable genetic model for studying human diseases. Adult flies were exposed to marijuana for variable time periods and the effects on cardiac function were studied. Short treatment protocol incremented heart-rate variability. Contractility was augmented only under prolonged exposure to cannabis and itwas associated with incremented calcium transient within cardiomyocytes. Neither the activity of the major proteins responsible for calcium handling nor the calcium load of the sarcoplasmic reticulum were affected by the cannabis treatment. The observed changes manifested in the cardiomyocytes even in the absence of the canonical cannabinoid receptors described in mammals. Our results are the first evidence of the in vivo impact of phytocannabinoids in D. melanogaster. By providing a simple and affordable platformprior to mammalian models, this characterization of cardiac function under marijuana exposure opens new paths for conducting genetic screenings using vaporized compounds.